Improving Hepatocyte Engraftment Following Hepatocyte Transplantation Using Repeated Reversible Portal Vein Embolization in Rats. Issue 1 (4th January 2019) - Gaillard, Martin; Tranchart, Hadrien; Lainas, Panagiotis; Trassard, Olivier; Remy, Séverine; Dubart‐Kupperschmitt, Anne; Dagher, Ibrahim
Abstract : Hepatocyte transplantation (HT) has emerged as a promising alternative to orthotopic liver transplantation, yet liver preconditioning is needed to promote hepatocyte engraftment. A method of temporary occlusion of the portal flow called reversible portal vein embolization (RPVE) has been demonstrated to be an efficient method of liver preconditioning. By providing an additional regenerative stimulus, repeated reversible portal vein embolization (RRPVE) could further boost liver engraftment. The aim of this study was to determine the efficiency of liver engraftment of transplanted hepatocytes after RPVE and RRPVE in a rat model. Green fluorescent protein–expressing hepatocytes were isolated from transgenic rats and transplanted into 3 groups of syngeneic recipient rats. HT was associated with RPVE in group 1, with RRPVE in group 2, and with sham embolization in the sham group. Liver engraftment was assessed at day 28 after HT on liver samples after immunostaining. Procedures were well tolerated in all groups. RRPVE resulted in increased engraftment rate in total liver parenchyma compared with RPVE (3.4% ± 0.81% versus 1.4% ± 0.34%; P < 0.001). In conclusion, RRPVE successfully enhanced hepatocyte engraftment after HT and could be helpful in the frame of failure of HT due to low cell engraftment.